Magnetic thickness measurement for various iron steels using magnetic sensor and effect of electromagnetic characteristics - Tsukada, Keiji; Hayashi, Minoru; Kawakami, Taisei; Adachi, Shoya; Sakai, Kenji; Kiwa, Toshihiko; Ishikawa, Toshiyuki; Mohd Mawardi, Saari; Hori, Kengo; Hisazumi, Kazumasa; Tominaga, Tomonori (American Institute of Physics Inc., 2022)
The diagnosis and prevention of the deterioration of iron-steel infrastructure has become an important social issue in recent years. The thickness measurement technique (extremely low-frequency eddy current testing (ELECT)) using a magnetic sensor for detecting steel corrosion at extreme frequency ranges has been previously reported. Using the calibration curves based on the correlation between the phase of the detected magnetic signal and the plate thickness, the plate thickness reduction caused by corrosion can be estimated from the detected phase signal. Iron-steel materials have large changes in electromagnetic characteristics; therefore, the reference calibration data for each type of iron-steel are required for plate thickness estimation. In this study, the effect of electromagnetic characteristics on the magnetic thickness measurement was investigated to improve the thickness estimation. Four types of iron-steel plates (SS400, SM400A, SM490A, and SMA400AW) with thicknesses ranging from 1 mm to 18 mm were measured by ELECT, and the phase change at multiple frequencies of each plate were analyzed. The shift in the phase and linearity regions of the calibration curves for each type of steel plate was observed. To analyze this shift phenomenon, the electromagnetic characteristics (permeability μ and conductivity σ) of each type of steel were measured. Compared with the permeability μ and conductivity σ of each steel plate in the applied magnetic field strength range, the product (σμ) for various steel plates decreased in the following order: SM400 > SS400 >SMA400AW > SM490A. The product of μ and σ is related to the skin depth, indicating the electromagnetic wave attenuation and eddy current phase shift in the material. Therefore, each shift in the calibration curve of each type of iron steel is explained by the changes in the parameters σ and μ.